Prolonged viral replication and longitudinal viral dynamic differences among respiratory syncytial virus infected infants - Brint, Monica E; Hughes, Joshua M; Shah, Aditya; Miller, Chelsea R; Harrison, Lisa G; Meals, Elizabeth A; Blanch, Jacqueline; Thompson, Charlotte R; Cormier, Stephania A; DeVincenzo, John P (Pediatric research, 2017)
Background Longitudinal respiratory syncytial virus (RSV) dynamics have not been well studied despite the existence of factors favoring prolonged RSV replication including high mutation rates allowing rapid evolution and potential escape from immune control. We therefore measured viral load in previously RSV-naive infants over prolonged time spans. Methods During 2014–2015, quantitative nasal aspirates were collected from 51 RSV-PCR+ infants. Multiple parallel assessments of viral loads were quantified at each collected time point using a well-validated real-time quantitative reverse transcriptase polymerase chain reaction assay. After observing viral load rebound phenomenon in some infants, the viral dynamics of 27 infants with sufficient longitudinal viral load data points were analyzed using the pre-defined criteria for viral rebound. Additional analyses were performed comparing age with viral rebound, viral clearance rates, and viral load area-under-the-curve (AUC VL ). Results The 51 infants (303 nasal aspirate samples; mean of 5.9 per patient) exhibited slower than expected viral clearance. Lower age trended toward slower viral clearance and greater AUC VL . Six infants had detectable viral loads ≥1 month after symptom onset. Ten of twenty-seven evaluable subjects exhibited viral rebound and this rebound was age-dependent ( P =0.0259). All but one rebounder were <70 days old. Conclusion Infants struggle to control primary RSV infections allowing prolonged viral replication and previously undescribed viral rebound; likely representing viral mutational immune escape.